2011
DOI: 10.1016/j.elspec.2010.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission spectra of frozen rock salt Pb1−xCdxTe crystal

Abstract: a b s t r a c tThe bulk single crystals of Pb 1−x Cd x Te were obtained by self-selecting vapor growth (SSVG) method with proper quenching. Tunable high energy X-ray photoemission spectroscopy (THE-XPS) and ultraviolet photoemission spectroscopy (UPS) were applied to study the crystals electronic structure of valence band and core level regions. The valence band density of states distribution spectra remarkably changes with the crystal composition. In most cases obtained valence band spectra of ternary crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…56 Although not impossible, the investigation of bulk Pb 1−x Cd x Te solid solutions by photoelectron spectroscopy, for a small content of Cd, did not display the existence of shoulders at low binding energies in the Pb 5d core-level spectrum. 57,58 Moreover, recent experiments have shown that ion exchange certainly proceeds in a layer-by-layer fashion, preventing a strong intermixing between Pb and Cd atoms. 59,60 Therefore, the well-resolved component seen on the Pb 5d core level at the lowest binding energy indicates that Pb exists in excess on the few PbSe facets at the surface of the HNCs and, possibly, on the CdSe surface of the shell.…”
Section: Pbmentioning
confidence: 99%
“…56 Although not impossible, the investigation of bulk Pb 1−x Cd x Te solid solutions by photoelectron spectroscopy, for a small content of Cd, did not display the existence of shoulders at low binding energies in the Pb 5d core-level spectrum. 57,58 Moreover, recent experiments have shown that ion exchange certainly proceeds in a layer-by-layer fashion, preventing a strong intermixing between Pb and Cd atoms. 59,60 Therefore, the well-resolved component seen on the Pb 5d core level at the lowest binding energy indicates that Pb exists in excess on the few PbSe facets at the surface of the HNCs and, possibly, on the CdSe surface of the shell.…”
Section: Pbmentioning
confidence: 99%
“…The single crystals of (Pb,Cd)Te solid solution containing 2% of CdTe as well as pure PbTe were grown by SSVG method at the Institute of Physics PAS [8][9][10][11]. The structure quality of samples and the chemical composition of the (Pb,Cd)Te solid solution were determined by X-ray powder diffraction utilizing X'Pert Philips (PANalytical) diffractometer and the Cu K α1 radiation.…”
Section: Experimental and Calculation Detailsmentioning
confidence: 99%
“…However, CdTe is a semiconductor crystallizing in the zinc blende structure and the difference in PbTe and CdTe crystal symmetry for many years was a reason for serious difficulties in a growth of (Pb,Cd)Te solid solution. Recent successful growth of big, metastable (Pb,Cd)Te crystals with the RS structure by self-selecting vapour growth (SSVG) method in the Institute of Physics PAS changed this situation [8][9][10][11]. Due to the application of SSVG technique solid solution containing up to 12% of CdTe can be obtained in the form of single crystals with the volume exceeding 1 cm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009 several physical properties of these crystals have been both investigated and reported (see, e.g., [11][12][13][14]). Quite recently, we have examined selected mechanical properties of this particular semiconductor.…”
Section: Introductionmentioning
confidence: 99%